Pola asuh keluarga desa mengantisipasi resiko penggunaan teknologi informasi dan komunikasi - Warsiyah Warsiyah; Muhammad Alfandi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
The risk of using information technology and communication (ICT) in children depends on how parents oversee and direct them. Need a relevant parenting in facing the risk of typing ICT. The purpose of this study is to find out how the family custody is right in anticipating the risk of information technology and communication. Data was obtained through observation and in-depth interviews in randomly selected parents sampling. Data analysis techniques in descriptive qualitative way with phenomenological approaches. The results showed that there were several parenting applied, namely permissive, authoritarian and democratic custody. The variations of the custody are influenced by several factors including the level of education of parents, the type of work of parents, social economic status of the family, the level of religiosity of parents, and the age of the child's age. Meanwhile the obstacles of parents in anticipating the negative impact of the use of information technology and communication include time limitations of overseeing children because both parents both work, the playing environment that average uses smart phones, parents do not have the ability to operate media information and communication so it is difficult Control what children do in the use of ICT.Â Â